Transportation noise and risk of stroke: a nationwide prospective cohort study covering Denmark. (23rd March 2021) - Sørensen, Mette; Poulsen, Aslak Harbo; Hvidtfeldt, Ulla Arthur; Münzel, Thomas; Thacher, Jesse Daniel; Ketzel, Matthias; Brandt, Jørgen; Christensen, Jesper H; Levin, Gregor; Raaschou-Nielsen, Ole
Abstract: Background: Studies on transportation noise and incident stroke are few and inconclusive. We aimed to investigate associations between road-traffic and railway noise and the risk of incident stroke in the entire Danish population. Methods: We estimated road-traffic and railway noise (Lden ) at the most and least exposed façades for all residential addresses across Denmark (2.8 million) for the period 1990–2017. Based on this, we estimated the 10-year time-weighted mean noise exposure for 3.6 million Danes aged >35 years, of whom 184 523 developed incident stroke during follow-up from 2000 to 2017. Analyses were conducted using Cox proportional-hazards models, with adjustment for various individual- and area-level demographic and socio-economic covariates collected from registries and air pollution [fine particulate matter with particles with a diameter of ≤2.5 µm (PM2.5 ) and nitrogen dioxide (NO2 )]. Results: A 10-dB increase in the 10-year mean road-traffic noise at the most exposed façade was associated with an incidence rate ratio (IRR) of 1.04 [95% confidence interval (CI): 1.03–1.05] for all strokes. For road-traffic noise at the least exposed façade, the IRR per 10 dB was 1.03 (95% CI: 1.02–1.04) for all strokes. Railway noise was not associated with a higher risk of stroke. Conclusion: Road-traffic noise increased the risk of stroke. These findings add to the evidence of road-traffic noise as a cardiovascular risk factor.